Does Benevolent Leadership Always Lead to Organizational Citizenship Behavior? The Mediated Moderation Effect of Manipulative Intention and Trust - Chia-Wu, Lin; Wan-Hsien, Hu; Jian-Bin Shih; 林家五; 胡宛仙; 施建彬 (Tai Da Guan Li Lun Cong, 2017)
Drawing on the attribution theory of leadership process, the subordinates’ attribution of intention about leaders’ behavior will affect their emotion and behavior. To address the attribution-consequence process, we hypothesize that perception of leaders’ manipulative intention moderated the positive relationship between benevolent leadership and trust, (i.e., in supervisor and organization) and organizational citizenship behavior, a mediated moderation model was proposed and tested. Two-wave data collected from 340 subordinates displayed results which demonstrated that benevolent leadership was less positively or even negatively related to trust and OCB when subordinates perceived high manipulative intention of their leaders’ behavior. On the contrast, benevolent leadership was positively related to trust and OCB when subordinates perceived low manipulative intention. Another finding is that benevolent leadership is most effective when they interact with the manipulative intention–the interaction effect on OCB partially mediated by trust in supervisor and organization. Finally, research limitations and suggestions for future research are also discussed.